Treatment of streptozotocin-induced diabetic rats with Castanea sativa and Lactarius deterrimus extracts decreases liver damage by initiating activation of the Akt prosurvival kinase - Mihailović, Mirjana; Uskoković, Aleksandra; Arambašic Jovanović, Jelena; Grdović, Nevena; Dinić, Svetlana; Poznanović, Goran; Franić, Aida; Đorđević, Marija; Vidaković, Melita (Archives of Biological Sciences, 2020)
Paper description: The effects of Castanea sativa and Lactarius deterrimus extracts on the mechanisms of hepatoprotection in streptozotocin-induced diabetic rats were studied. Both extracts caused activation of the prosurvival-Akt kinase and decreases in O-GlcNAc-modified antioxidant enzymes and NF-κB, collagen fiber deposition, and proinflammatory signaling. The hyperglycemia-reducing and antioxidant effects of the extracts suppressed cytotoxic signaling pathways and attenuated diabetes complications in the liver. The extracts are beneficial in the prevention of liver damage. The extracts could be considered for prediabetes and diabetes management after a definitive phytochemical description of extract constituents and their evaluation in preclinical and clinical studies. Abstract: Diabetes is the most important non-infectious disease affecting 5% of the general population. Different plant and mushroom extracts with hypoglycemic and antioxidant properties have been used traditionally as antidiabetic herbal medicines. The aim of this study was to study the in vivo effect of extracts obtained from the edible mushroom, Lactarius deterrimus (Ld), and chestnut, Castanea sativa (Cs), on the alleviation of liver damage in streptozotocin (STZ)-induced diabetic rats. The extracts were applied, either alone or in combination, for four weeks, starting from the last day of STZ administration. Diabetic rats treated with the extracts exhibited reduced hyperglycemia and lower hepatic oxidative stress. Extract treatment decreased the level of O-linkage of N-acetylglucosamine modified superoxide dismutase, catalase and NF-κB. Masson trichrome staining showed a decrease in collagen fiber deposition in the liver. Immunoblot analysis revealed the activation of the prosurvival Akt kinase after extract application. The obtained results revealed that the hyperglycemia-reducing and antioxidant effects of the Ld and Cs extracts suppressed cytotoxic signaling pathways, attenuating the negative effects of diabetes on the liver. The examined extracts are beneficial in the prevention of liver damage and could be considered for prediabetes and diabetes management after a definitive phytochemical description of extract constituents and subsequent evaluation in preclinical and clinical studies. https://doi.org/10.2298/ABS200410017M Received: April 10, 2020; Revised: April 18, 2020; Accepted: April 20, 2020; Published online: April 22, 2020 How to cite this article: Mihailović M, Uskoković A, Arambašić Jovanović J, Grdović N, Dinić S, Poznanović G, Franić A, Đorđević M, VidakovićM. Treatment of streptozotocin-induced diabetic rats with Castanea sativa and Lactarius deterrimus extracts decreases liver damage by initiating activation of the Akt prosurvival kinase. Arch Biol Sci. 2020;72(2):233-42.